Rates of injection in prison in a sample of Australian injecting drug users - Fetherston, James; Carruthers, Susan; Butler, Tony; Wilson, David; Sindicich, Natasha (Informa Healthcare, 2013)
Aims: Determine the prevalence and frequency at which injecting drug users (IDU) continue to inject whilst incarcerated and to identify factors associated with in-prison injecting. Design: A nationally coordinated cross-sectional convenience sample. Participants: A total of 355 regular IDUs who had been imprisoned within the past 10 years. Measurements: Data concerning demographics, drug use history and injection whilst imprisoned were collected by participant self-report. Findings: Almost half, 46% (n = 162), of the participants reported that they had ever injected whilst imprisoned. Most of these (n = 150; 42% of all participants) reported injecting during their last imprisonment. Factors identified as significantly associated with prison injecting were being male, receiving income from criminal activity in the month prior to interview and length of last sentence. Frequency of injection varied from isolated instances to multiple times daily. Half (n = 75) of those who injected during their most recent imprisonment reported injecting at a lower frequency while incarcerated than they did in the month prior to survey. Two individuals reported initiation to injection during their most recent period of imprisonment. Conclusions: Most IDUs who experience imprisonment either suspend injecting whilst incarcerated or reduce the frequency at which they inject. However, injection is still common in Australian prisons, highlighting the need for continued harm-minimisation efforts with this population.